A Bacteriochlorin‐Based Metal–Organic Framework Nanosheet Superoxide Radical Generator for Photoacoustic Imaging‐Guided Highly Efficient Photodynamic Therapy. Issue 14 (16th May 2019) - Zhang, Kai; Yu, Zhaofeng; Meng, Xiangdan; Zhao, Weidong; Shi, Zhuojie; Yang, Zhou; Dong, Haifeng; Zhang, Xueji
Abstract: Hypoxic tumor microenvironment is the bottleneck of the conventional photodynamic therapy (PDT) and significantly weakens the overall therapeutic efficiency. Herein, versatile metal–organic framework (MOF) nanosheets (DBBC‐UiO) comprised of bacteriochlorin ligand and Hf6 (µ3 ‐O)4 (µ3 ‐OH)4 clusters to address this tricky issue are designed. The resulting DBBC‐UiO enables numerous superoxide anion radical (O2 − ) generation via a type I mechanism with a 750 nm NIR‐laser irradiation, part of which transforms to high toxic hydroxyl radical (OH) and oxygen (O2 ) through superoxide dismutase (SOD)‐mediated catalytic reactions under severe hypoxic microenvironment (2% O2 ), and the partial recycled O2 enhances O2 − generation. Owing to the synergistic radicals, it realizes advanced antitumor performance with 91% cell mortality against cancer cells in vitro, and highly efficient hypoxic solid tumor ablation in vivo. It also accomplishes photoacoustic imaging (PAI) for cancer diagnosis. This DBBC‐UiO, taking advantage of superb penetration depth of the 750 nm laser and distinct antihypoxia activities, offers new opportunities for PDT against clinically hypoxic cancer. Abstract : A new‐style of bacteriochlorin‐based metal–organic frameworks (MOFs) nanosheets termed DBBC‐UiO is developed as an NIR laser‐induced O2 − generator for photoacoustic imaging‐guided photodynamic therapy through synergistic types I and II mechanism for hypoxia tumor ablation. Under 750 nm NIR irradiation, DBBC‐UiO enables the generation of abundant O2 − in the hypoxic microenvironment, resulting in cell apoptosis.